2021
DOI: 10.3390/biomedicines9080958
|View full text |Cite
|
Sign up to set email alerts
|

Refractory Pediatric Psoriasis and Atopic Dermatitis: The Importance of Therapeutical Adherence and Biological Management

Abstract: The rates of refractory pediatric psoriasis and atopic dermatitis (AD) have steadily risen over the last few decades, demanding newer and more effective therapies. This review aims to explore the reasons for resistant disease, as well as its management; this includes the indications for, efficacy of, and safety of current therapies for refractory pediatric dermatologic disease. A PubMed search for key phrases was performed. Poor medication adherence is the most common cause of resistant disease and may be mana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Considering all treatment options and scenarios mentioned above, a review of the literature has identified the following guidelines and strategies to successfully manage treatment-resistant or refractory cases of AD in pediatric patients. 6,9,77,78 (Fig. 2).…”
Section: Strategies To Manage Treatment-resistant Pediatric Ad Casesmentioning
confidence: 99%
“…Considering all treatment options and scenarios mentioned above, a review of the literature has identified the following guidelines and strategies to successfully manage treatment-resistant or refractory cases of AD in pediatric patients. 6,9,77,78 (Fig. 2).…”
Section: Strategies To Manage Treatment-resistant Pediatric Ad Casesmentioning
confidence: 99%
“…Despite their efficacy and safety, in France, the current initial prescription (the first biological therapy) and annual hospital renewal policy may impact patient adherence, especially that of patients who have difficulties accessing hospital services. Apart from one study which assessed the importance of therapeutical adherence and biological management in paediatric patients with psoriasis or AD, we have not found any investigation or research on this subject in existing literature for AD 3 …”
mentioning
confidence: 99%